Geometric regulation of kinetochore orientation - Watanabe, Yoshinori (Henry Stewart Talks, 2009)
The cell cycle, Aurora B-dependent destabilization, The attachment is stabilized under tension, Tension-dependent reorientation, Kinetochore geometry, Organization of centromeres, Budding yeast, Two models to account for the mono-polar attachment at meiosis I, Rec8 vs. Rad21 at the centromere, Cohesion-mediated kinetochore orientation model, Is the central core cohesion defective in moa1Δ?, A lacO array in the core centromere, Excision of core centromeres, Cohesion at core centromeres depends on Moa1 as well as Rec8, Cohesion at core centromeres is disrupted at prophase II, Centromeric resolution in mitosis, Core centromere is intrinsically prevented from establishment of cohesion, Artificial tether at the core centromere, Opposite effects of tethers at the core and peri-centromeric regions
Archived at 2020/01/15